Żegluga lotnicza a wymagania dla statków powietrznych i ich załóg oraz zezwolenia na określone rodzaje lotów – wybrane zagadnienia prawne - Podraza, Marek (PRAWO i WIĘŹ, 2025)
The safety of air navigation is one of the greatest challenges and priorities facing public international law, EU law and the national law of individual countries. Undoubtedly, the elements that increase its level are uniform regulations regarding aircraft and their crews, nationality, and permits to perform specific types of flights. From this perspective, it is worth analyzing existing legal provisions – adopted within the International Civil Aviation Organization (ICAO), as well as those adopted within individual countries – and considering actions that could have further positive effects in the future.